2008
DOI: 10.1534/genetics.107.082370
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Centric Genomewide Association Study via Entropy

Abstract: Genes are the functional units in most organisms. Compared to genetic variants located outside genes, genic variants are more likely to affect disease risk. The development of the human HapMap project provides an unprecedented opportunity for genetic association studies at the genomewide level for elucidating disease etiology. Currently, most association studies at the single-nucleotide polymorphism (SNP) or the haplotype level rely on the linkage information between SNP markers and disease variants, with whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 40 publications
0
50
0
Order By: Relevance
“…In summary, this truncated tail strength method can be applied to any dataset for an overall hypothesis of no association between multiple features and an outcome of interest, such as in microarray analysis, haplotype-based analysis, and gene-based analysis (Cui et al, 2008), pathway-based analysis (Yu et al, 2009) and so on. Furthermore, the R and MATLAB programs (tts.R and tts.m) used in the simulation can be available by request.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, this truncated tail strength method can be applied to any dataset for an overall hypothesis of no association between multiple features and an outcome of interest, such as in microarray analysis, haplotype-based analysis, and gene-based analysis (Cui et al, 2008), pathway-based analysis (Yu et al, 2009) and so on. Furthermore, the R and MATLAB programs (tts.R and tts.m) used in the simulation can be available by request.…”
Section: Discussionmentioning
confidence: 99%
“…Even approaches that are not directly founded on entropy, such as Bayesian methods, sometimes include components that are best termed "relative entropy" (see Appendix) [90]. Cui [91] extend beyond single SNP-disease association to incorporate all SNPs in a gene simultaneously, using an entropy measure to summarize the interaction between all SNPs and the disease state. They showed that this has greater power than an approach that deals with each SNP independently.…”
Section: S H(c) Are Independent Of the Highest-level Interaction In mentioning
confidence: 99%
“…Therefore, some innovative methods focus on case-only designs. One such approach utilizes entropy-based statistics [14] [15]. The entropy is used to measure the uncertainly of random variables.…”
Section: Current Approaches To Identify Epistasismentioning
confidence: 99%